The Trans-Atlantic Trade and Investment Partnership – A Challenge for the European Union? - Oana–Antonia Colibășanu; Victor Vlad Grigorescu (Romanian Journal of European Affairs)
Since the early 2000s, the United States and European Union have discussed the development of bilateral and regional trade agreements. The TTIP – Trans-Atlantic Trade and Investment Partnership was announced in February 2013 and is currently under negotiation. The initiative aims at establishing a trade agreement between the two blocs, removing all trade barriers, including the non-tariff ones, in a wide range of economic sectors. The paper looks at several key elements that the bilateral negotiations are set to challenge from the European Union perspective. We focus on the main causes for resistance within the EU towards establishing the agreement, seeking to understand the future framework for international trade for the European states. While the EU continues integration to establish a functioning internal market, still continuing the process of diminishing and eliminating non-tariff barriers among the member states, we examine whether liberalisation of trade and investment between the US and the EU will benefit the EU as a whole, considering the current socio-economic trends at the Union’s level.